Transcriptomic identification of iron-regulated and iron-independent gene copies within the heavily duplicated Trichomonas vaginalis genome - Horváthová, Lenka; Šafaríková, Lucie; Basler, Marek; Hrdy, Ivan; Campo, Neritza B; Shin, Jyh-Wei; Huang, Kuo-Yang; Huang, Po-Jung; Lin, Rose; Tang, Petrus; Tachezy, Jan (Genome biology and evolution, 2012)
Gene duplication is an important evolutionary mechanism and no eukaryote has more duplicated gene families than the parasitic protist Trichomonas vaginalis. Iron is an essential nutrient for Trichomonas and plays a pivotal role in the establishment of infection, proliferation, and virulence. To gain insight into the role of iron in T. vaginalis gene expression and genome evolution, we screened iron-regulated genes using an oligonucleotide microarray for T. vaginalis and by comparative EST (expressed sequence tag) sequencing of cDNA libraries derived from trichomonads cultivated under iron-rich (+Fe) and iron-restricted (-Fe) conditions. Among 19,000 ESTs from both libraries, we identified 336 iron-regulated genes, of which 165 were upregulated under +Fe conditions and 171 under -Fe conditions. The microarray analysis revealed that 195 of 4,950 unique genes were differentially expressed. Of these, 117 genes were upregulated under +Fe conditions and 78 were upregulated under -Fe conditions. The results of both methods were congruent concerning the regulatory trends and the representation of gene categories. Under +Fe conditions, the expression of proteins involved in carbohydrate metabolism, particularly in the energy metabolism of hydrogenosomes, and in methionine catabolism was increased. The iron-sulfur cluster assembly machinery and certain cysteine proteases are of particular importance among the proteins upregulated under -Fe conditions. A unique feature of the T. vaginalis genome is the retention during evolution of multiple paralogous copies for a majority of all genes. Although the origins and reasons for this gene expansion remain unclear, the retention of multiple gene copies could provide an opportunity to evolve differential expression during growth in variable environmental conditions. For genes whose expression was affected by iron, we found that iron influenced the expression of only some of the paralogous copies, whereas the expression of the other paralogs was iron independent. This finding indicates a very stringent regulation of the differentially expressed paralogous genes in response to changes in the availability of exogenous nutrients and provides insight into the evolutionary rationale underlying massive paralog retention in the Trichomonas genome.
Keywords: Gene Dosage; železo; Genes, Protozoan; Expressed Sequence Tags; Gene Library; Iron-Sulfur Proteins; Transcriptome; Genome, Protozoan; Cysteine Proteases; Trichomonas vaginalis; cysteinové proteasy; genom protozoální; genová knihovna; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; molekulární evoluce; duplikace genu; Oligonucleotide Array Sequence Analysis; exprimované sekvenční adresy; Glycolysis; Gene Expression Regulation; Iron; Gene Duplication; transkriptom; regulace genové exprese; glykolýza; Evolution, Molecular; genová dávka; proteiny obsahující železo a síru; protozoální geny